PENGARUH DIFERENSIASI PRODUK, INOVASI DAN NILAI TRADISIONAL TERHADAP KEUNGGULAN BERSAING UKM BATIK SUMENEP DIMEDIASI KAPABILITAS PEMASARAN DI TENGAH PERSAINGAN GLOBAL - rahman, fathor (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Wiraraja, 2025)
This study aims to analyze the effect of product differentiation, innovation, and traditional values on the competitive advantage of batik SMEs in Sumenep Regency, with marketing capability as a mediating variable amid global market competition. A quantitative approach was employed using Partial Least Square Structural Equation Modeling (PLS-SEM). The research sample consisted of 125 batik business owners selected through purposive sampling. The research instrument was validated through reliability, convergent validity, and discriminant validity testing. The results show that product differentiation has a significant direct effect on competitive advantage but does not significantly influence marketing capability. Innovation significantly affects both competitive advantage and marketing capability, although the direction of the effect on marketing capability is negative. Traditional values positively influence marketing capability but have a negative direct effect on competitive advantage. Marketing capability demonstrates a strong and significant positive influence on competitive advantage and effectively mediates the influence of traditional values and innovation. These findings highlight the strategic role of marketing capability in transforming internal potential into sustainable competitive advantage. The implication of this study suggests that adaptive and integrated marketing strategies are essential for aligning differentiation, innovation, and cultural values to enhance the competitiveness of batik SMEs in both domestic and global markets.